Learner's privilege and responsibility : a critical examination of the experiences and perspectives of learners from Chinese backgrounds in the United States - Ma, Wen; Wang, Chuang (Language, literacy, and learning., 2014)
This book is about the learner side of the teaching and learning equilibrium, centering on the educational experiences and perspectives of Chinese students in the United States. These students ranged from kindergarteners, adolescents, undergraduate, graduate, to adult learners, across the educational spectrum. Because Chinese students are the largest cohort among all international students in the U.S., and their prior educational experiences and perspectives in China are so different from those in the U.S., exploring who they are, what their learning experiences have been, and how their learning needs can be better met, may not only allow U.S. educators to teach them more effectively, but also help the educational community in both countries better learn about and from each other.The chapters in the book examine the constructs of learner privilege and responsibility in the teaching and learning equation, cultural and linguistic challenges and transitional adjustments, self-concept, learning strategies, comparison and contrast of differences and similarities between Chinese and American students, and/or critical reflections on significant issues confronting Chinese learners. While each chapter is situated in its own research literature and connects with its own teaching and learning practices, all of them are united around the overarching themes of the book: the experiences and perspectives of diverse learners from Chinese backgrounds in the United States. The chapters also flesh out some of the larger theoretical/pedagogical issues between education in China and in the United States, provide useful lenses for rethinking about and better understanding their differences and similarities, as well as offer pertinent suggestions about how the educational community in both countries may benefit from learning about and from each other.